PENINGKATAN KAPASITAS LITERASI DIGITAL PADA GURU SEKOLAH DASAR DALAM PEMBUATAN BAHAN AJAR KREATIF DAN INOVATIF - Tiara Eka Putri; Mayang T. Afriwilda; Ike Kurniawati (GANESHA: Jurnal Pengabdian Masyarakat, 2024)
Digital literacy provides a new color in the world of education, where technology becomes part of education itself. In providing learning, teachers can utilize technology as a learning resource. One of the partner problems in this service activity is the lack of utilization of technology and the limited knowledge of teachers about websites or learning resource service provider tools that can be accessed for free in developing creative and innovative teaching materials. This activity aims to increase the capacity of digital literacy in elementary school teachers. The target audience in this community service activity is teachers at SDN 52 Bengkulu City totaling 30 people. The method of implementing this community service is carried out in 4 stages, namely preparation and identification, practice, assistance, evaluation. The results of the activity showed that the training participants experienced an increase in understanding and experience related to the use of websites as a source of teaching materials. There was a significant increase in understanding of websites providing teaching materials and making creative and innovative teaching materials. Participants also showed an increase in knowledge about the website address of teaching material providers and the ability to use the features on the website.